1999
DOI: 10.2105/ajph.89.12.1827
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a social influences smoking prevention program as a function of provider type, training method, and school risk.

Abstract: comes with seventh graders who were "experimental smokers" at the outset but worse results among baseline "smokers" (both treatment conditions had an iatrogenic effect with baseline "smokers," but boomerang effects were largest in teen leader schools).Questions also arise about how providers should be trained. Although conceptual frameworks have been developed to guide training activities,'4"5 and influential guide-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 23 publications
9
77
0
3
Order By: Relevance
“…Previous studies have not randomly assigned both implementer types within the same schools (e.g., Cameron et al, 1999;McNeal et al, 2004). The second strength of our study is the use of observer assessments of program fidelity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have not randomly assigned both implementer types within the same schools (e.g., Cameron et al, 1999;McNeal et al, 2004). The second strength of our study is the use of observer assessments of program fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a paucity of studies on this topic. We found only two studies that systematically manipulated the type of implementer of a school-based substance abuse prevention program (Cameron et al, 1999;McNeal, Hansen, Harrington, & Giles, 2004). The study by McNeal and colleagues showed larger effects for classroom teachers, relative to outside program specialists, on substance use outcomes and mediating variables (McNeal et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This included two systematic reviews (Tilley andChambers, 2003, Wainwright et al, 2000), nine RCTs (Cameron et al, 1999, DeLago et al, 2001, Harrell et al, 1998, Hill et al, 1991, Lamb et al, 1998, Persaud et al, 1996, Puskar et al, 2003, Werch et al, 1996, Werch et al, 2003, one quasi RCT where allocation was by coin toss (Pike and Banoub-Baddour, 1991) and four non-randomised controlled trials (Allen, 2003, Long et al, 1975, Munodawafa et al, 1995, Skybo and Ryan-Wenger, 2002). …”
Section: Current Evidence Base For School Nursing Interventionsmentioning
confidence: 99%
“…medications) necessitate randomizing individuals, and the units providing the response are clustered within individuals. The many advantages of cluster randomization have led to its increased use in recent years in diverse areas of research including health promotion [7], education for disease management [8], clinical research [9], and health policy and program evaluation [10]. Donner and Klar [11] give a thorough account of the practical and methodological issues in the conduct of cluster-randomized trials.…”
Section: Introductionmentioning
confidence: 99%